2023
DOI: 10.15441/ceem.23.145
|View full text |Cite
|
Sign up to set email alerts
|

Explainable artificial intelligence in emergency medicine: an overview

Yohei Okada,
Yilin Ning,
Marcus Eng Hock Ong

Abstract: Artificial intelligence (AI) and machine learning (ML) have potential to revolutionize emergency medical care by enhancing triage systems, improving diagnostic accuracy, refining prognostication, and optimizing various aspects of clinical care. However, as clinicians often lack AI expertise, they might perceive AI as a “black box,” leading to trust issues. To address this, “explainable AI,” which teaches AI functionalities to end-users, is important. This review presents the definitions, importance, and role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Researchers from Turkey showed that there is a strong conviction among ED staff about the benefits of using AI support to assess a patient during triage; however, concerns about the related ethical aspects of such an intervention are also present among them [ 63 ]. Some of the misunderstandings about the idea of machine learning are addressed by the publications discussing the topic in more depth in the emergency medicine group [ 64 ].…”
Section: Future Of Triagementioning
confidence: 99%
“…Researchers from Turkey showed that there is a strong conviction among ED staff about the benefits of using AI support to assess a patient during triage; however, concerns about the related ethical aspects of such an intervention are also present among them [ 63 ]. Some of the misunderstandings about the idea of machine learning are addressed by the publications discussing the topic in more depth in the emergency medicine group [ 64 ].…”
Section: Future Of Triagementioning
confidence: 99%